Development of expert working groups and a learning management system within the Australian National Fabrication Facility. Issue 11 (2nd May 2021) - Jarvis, Karyn; Macky, Stephanie; Fitzpatrick, Jane
Abstract: The Australian National Fabrication Facility (ANFF) is a federally funded facility that provides real open access to state‐of‐the‐art microfabrication and nanofabrication facilities for both academic and industry researchers. The ANFF network has over 500 instruments spread across 20 sites in Australia. Since its inception in 2007, ANFF has grown to approximately 3000 users and 200, 000 user hours per year. As ANFF operations are spread across eight geographically separated nodes, such growth has demonstrated the need for more consistent processes across the organization. An expert working group program is being implemented to facilitate knowledge sharing between ANFF nodes within instrument groups. The development of an online learning management system is in progress to standardize training across ANFF to create a consistent learning experience. The goals of these two initiatives are to increase communication, share knowledge, standardize processes, reduce duplication, and increase quality across the Australia wide ANFF network. Abstract : The Australian National Fabrication Facility (ANFF) provides open access micro and nanofabrication facilities for both academic and industry researchers To increase communication, share knowledge, standardise processes, reduce duplication and increase quality across the ANFF network, an expert working group program and online learning magement system are currently under development.